(3CjGe dgG JGQjN (B/s - (3HgGA GdOjf, CMeOs ((3GdbGgQI(B. (3HjQhJ (B:s (3OGQ GdTQhb ,s, 1985)
(3GdCOHGJj(B, (3NWjH GdKhQI(B, (3RhGL GdTjN Ydj jhSa(B, (3ddLdGA(B, (3hGdOSJhQ(B, (3hGdafj GdLejd(B, (3GeHQGWhQjI RaJj(B, (3GdCeI Hjf SYO hYOdi(B, (3GdESdGe hCUhd GdMces
Keywords: (3GdCOH GdYQHjs; (3JGQjN s